Legal Feminization: Dissecting Gender Inequality in Judges' Decisions in Sexual Violence Cases - Henny Saida Flora; Henry Aspan (Journal of Strafvordering Indonesian, 2025)
This study examines the implementation of Law Number 12 of 2022 concerning the Crime of Sexual Violence (TPKS Law) in criminal justice practice with a focus on gender inequality in legal reasoning and judges' juridical arguments. The TPKS Law exists as a progressive legal instrument that emphasizes a victim-based approach and the principle of non-discrimination, as well as accommodates previously unrecognized forms of non-physical sexual violence. However, the effectiveness of these norms is still constrained by judicial practices that are often based on conventional legal paradigms and patriarchal biases. The normative juridical approach is used to analyze positive legal norms, court decisions, and feminist legal concepts, in order to assess the extent to which the principles of the TPKS Law are internalized by judges. The results of the study show that many decisions still question the credibility of victims and ignore the psychosocial dimension of sexual violence, thus perpetuating the practice of victimization. The low sensitivity of gender in legal considerations shows the need for legal feminization as an effort for epistemological and structural transformation in the judicial system. These findings underscore the importance of gender-sensitive judicial training and criminal procedure law reform so that the law can function as a means of substantive justice. This study recommends the integration of legal feminist values as a normative and interpretive framework in sexual violence cases.